The legal system of financing contracts concluded between Syria and the European Investment Bank (Damascus University Journal for legal sciences, 2025)
To finance its projects, State may resort to public or private foreign bodies. This applied to Syria which signed contracts with the European Investment Bank (EIB). One of these contracts aimed to finance a project for an electric power transmission, signed on Dec 14, 2000. Another one was to finance a project for an electric power distribution, signed on Feb 5, 2001.These financing contracts between Syrian and EIB are international contracts since they go beyond the borders of the state. Thus, two perceptions appear: first, as a banking transaction, since one of its parties is a bank that funds specific agents; second, as an international relation, since the party asking for the credit is a sovereign state receiving a fund from an international financial organization. Consequently, these contracts come with binary questions: as a banking transaction and as an international financial relation. This article investigates the former: the banking transaction, through which Syria receives a given fund from EIB, but where the legal nature of the contract is unclear. These contracts are similar to loan contracts in terms of general conditions, and they are similar to letters of credit in terms of characteristics, conditions, and parties’ obligations.In the context of what was mentioned, it is necessary to clarify the legal nature of these contracts as a banking transaction, similar to the other banking operations that the bank runs with its customers.
Keywords: Finance Contracts; European Investment Bank; Banking Transactions; Loan Contract; Credit Opening Contract